1994
DOI: 10.1136/oem.51.3.173
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the comparative intensity of pneumoconiotic changes caused by chronic inhalation exposure to dusts of different cytotoxicity by means of a mathematical model.

Abstract: A multicompartmental mathematical model has been used to simulate variations in the cytotoxicity of dusts in the kinetics of the retention, in the pulmonary region and tracheobronchial lymph nodes, of practically insoluble quartzite and titanium dioxide dust particles deposited on the free surfaces of the acini from alveolar air. Experiments with these dusts were conducted on rats exposed to virtually the same dust concentrations in the air for an experimental period of 20 weeks and a period of 10 weeks after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
15
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 8 publications
1
15
0
Order By: Relevance
“…The authors observed experimental silicosis but did not report an induction of lung tumors. A similarly close relationship may also exist for the studies by Privalova et al (1987) and Katsnelson et al (1994). Both studies probably used the same quartzite specimen, and the exposure concentrations were almost the same.…”
supporting
confidence: 50%
See 2 more Smart Citations
“…The authors observed experimental silicosis but did not report an induction of lung tumors. A similarly close relationship may also exist for the studies by Privalova et al (1987) and Katsnelson et al (1994). Both studies probably used the same quartzite specimen, and the exposure concentrations were almost the same.…”
supporting
confidence: 50%
“…Animal husbandry and analytical procedures of determining compartmental retention data may be other causes for discrepancies. Katsnelson et al (1994) quoted a methodical change in quartzite mass analysis and different particle sizes of the inhaled quartzite dust as partial causes for the observed differences between the two quartzite studies. Besides these systematic deviations, the actual data are scarce and show considerable scatter.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…They are hardly always living with chronic inflammation of the respiratory system. Meantime, it is long ago that we [96][97][98][99][100] found fairly strong reasons for considering the NL recruitment response to be an important mechanism of partial compensation for the damage caused by cytotoxic micrometric particles to AMs, the main effector of the pulmonary clearance. A mathematical multi-compartmental model of pulmonary region clearance which comprised just this compensatory mechanism simulated very well the pulmonary retention of dusts of varying degrees of cytotoxicity (quartzite rock, titanium dioxide, standard quartz DQ12) under long-term inhalation exposure as well as a decrease in this retention under the effect of such potent protectors of the macrophage against particle cytotoxicity as glutamate.…”
Section: Some Inferences From In Vivo Experiments With Metallic Nanopmentioning
confidence: 99%
“…It was found that this recruitment is controlled by the mass of macrophage breakdown products (MBP) and especially by their lipid fraction. [96][97][98][99][100] Therefore, the more cytotoxic for AMs are particles deposited in the lungs (or the higher the dose of MBPs obtained by aseptic freezingthawing or ultrasonic destruction of non-activated peritoneal macrophages and then instilled intratracheally), the higher is a count ratio of NLs to AMs in the BALF. Therefore this ratio (NL/AM) can be used as an indirect but highly informative comparative in vivo index for the cytotoxic action of any low-soluble particle, and it was demonstrated that ranking of dusts by this index was well correlated with the ranking of their cytotoxicity based on the Trypan blue exclusion test for cell viability in vitro.…”
mentioning
confidence: 99%